Interior of The Study and Play Room: It’s Relationship to The Physical Development of The Child's Motor - Armanila Armanila; Nurul Zahrani Jf; Veryawan Veryawan (AT-TURATS, 2022)
This study aims to find out the early childhood motor development contained in RA Rabbani Islamic School, how to implement the interior of the learning room and play on the physical development of children's motor and see the relationship. The research was conducted at RA Rabbani Islamic School located in Medan City, Medan Helvetia Subdistrict. The method used is qualitative with a phenomenological approach and data collection techniques through observation, interviews, documentation. Then, researchers perform data analysis techniques to compile the data obtained and finally, namely performing data validity techniques through source triangualization, engineering triagulation and time triangulation. The results showed that children's motor development is at a level of developing as expected, because in the implementation of the interior of the study and play room at RA Rabbani Islamic School is very concerned about the shape, color, lighting, texture, variability, material concept, and size of the interior, therefore there is a connection between the interior of the study room and play on the physical development of early childhood motor, From 15 children, there are 11 children who have achieved development as expected (BSH), and 4 children who are very well developed (BSB). If indicated, then the average value is 86, meaning that it has exceeded the value limit of 80, which is determined as the completion value of development achievements.